The "Fame Effect" or How the syntactic choices of writers can be explained by their assumptions about their addressees' state of knowledge: the case of relevance-oriented, non-restrictive noun modifiers - Rudy Loock (Discours)
In this paper we would like to explore, within Vallduví’s (1992, 1993) information packaging theory, how writers’ assumptions about their addressees’ state of knowledge can account for the choice writers make between competing syntactic structures, which we call “allostructures”, to convey the same informational content. The assumed old/new informational status has then an influence on the grammatical choices made by the writers. In particular we investigate here, using the web as corpus, the constraints that govern writers’ choice between the following non-restrictive modifiers of nouns that aim at optimizing the relevance (as defined by Sperber & Wilson) of the referents denoted by the nouns they modify: nominal appositives, appositive relative clauses, non-restrictive pre-modifiers.